Discharge readiness and its influencing factors among pregnant women with gestational diabetes mellitus (妊娠期糖尿病产妇出院准备度现状及影响因素研究) - DUAN Meimei (段美美); SUN Guiyu (孙贵豫); LI Yuanyuan (黎媛媛) (中西医结合护理)
Objective To investigate the status quo of hospital readiness of pregnant women with gestational diabetes mellitus (GDM) and analyze its main influencing factors. Methods Objective sampling method was used to select 118 pregnant women with GDM in a grade A hospital as the research object. The general information questionnaire, Readiness for Hospital Discharge Study-New Mother Form(RHDS-NMFS), Quality of Discharge Teaching Scale New Mother Form(OB-QDTS) were performed to collected data and the related factors affecting the status quo of readiness for hospital discharge were analyzed. Results The score of RHDS-NMFS of GDM women was (118. 16±18. 36) points, which was at the medium level. There were statistically significant differences in RHDS-NMFS scores of GDM women with education, other pregnancy complications or complications, mode of postpartum confinement, understanding of gestational diabetes, and whether they usually monitored blood glucose by themselves (P＜0. 05). The total score of RHDS-NMFS was positively correlated with the total score of OB-QDTS (P＜0. 05). Education level, understanding of gestational diabetes mellitus, self-monitoring of blood glucose and quality of discharge guidance were the main influencing factors of discharge preparation for GDM parturients (P＜0. 05). Conclusion Medical staff can start from the main factors affecting the discharge readiness of GDM parturients, strengthen the explanation of disease knowledge, encourage parturients to self-measure blood sugar, improve the quality of discharge guidance, and thus improve their discharge readiness. (目的 调查妊娠期糖尿病(GDM)产妇出院准备度的现状, 分析其主要影响因素。方法 采用目的抽样法选取某三甲医院的118例GDM产妇作为调查对象, 选取一般资料调查表、产妇出院准备度量表(RHDS-NMFS)、产妇出院指导质量量表(OB-QDTS)进行相关调查, 分析影响出院准备度水平的相关因素。结果 GDM产妇RHDS-NMFS量表得分为(118. 16±18. 36)分, 处于中等水平。文化程度、有无其他妊娠合并症或并发症、“坐月子”方式、对GDM的了解程度、平常是否自己监测血糖的GDM产妇出院准备度得分差异有统计学意义(P＜0. 05); RHDS-NMFS量表总分与OB-QDTS量表总分呈正相关(P＜0. 05); 文化程度、对GDM的了解程度、平常是否自己监测血糖和出院指导质量是影响GDM产妇出院准备的主要因素(P＜0. 05)。结论 医护人员可从影响GDM产妇出院准备度的主要因素着手, 加强疾病知识的讲解, 鼓励产妇自测血糖, 提高出院指导质量, 从而提高其出院准备水平。)